Bisnis Nener dalam Perspektif Hukum Ekonomi Syariah (Studi Kasus CV. Simpatik Buleleng Bali) - Handayani, Eka (MOMENTUM : Jurnal Sosial dan Keagamaan, 2021)
This research was conducted to analyze the factual conditions in the milkfish business to find out local and export business at the CV. Simpatik Buleleng pond company, this research methods, types of research used is field research, collected data by researchers include primary and secondary data, while the source obtained by observation, interview, and documentation, then teh data is analyzed descriptively throuh, display, reduction, verification and prescriptive, so that it produces the result that is 1. Companies set prices unilaterally, islam provides freedom in specify prices by Wahbah Zuhaili, Ibnu Araby, Imam Malik, and Ibnu Taimiyah. 2. Nener sample calculation, becomes an agreement between siler and buyer. 3. The Fuqoha’ allow shigat fi’liyah (actions) clarity of sale and purchase transaction contracts, as well as exchanging goods using money this is allowed by Ibnu Qosim in the kitab athul qorib. 4. The high price of nener is allowed to use a Musawama sale and purchase contract (bargaining) 5. Ordering nener in larvae tuber not yet old enough to be harvested is a prohibition on buying and selling (gharar) by Imam Nawawi and Imam Al-Qorafi while according to Syafi’iyyah, Abu Yusuf Muhammad (Hanafiyah) and one narration of madhab Ahmad states that it is invalid, malikiyah and one narration of hanabilah that it is forbidden to buy and sell food that has not been received by hand. 6. Late payment of nener’s money, according to the argument of ijma’ by Ibnu Qoudamah rahimahullah stating that the sale and purchase is valid in accordance with the compensation given. 7.Nener’s death is the responsibility of the seller who should be the responsibility of the buyer, in this case it is contrary to the opinion of alqadhi and scholars who belong to his group namely goods that have been determined to be the responsibility of the buyer. 8. Payment via ATM is allowed because the ijab & qobul consent can be fulfilled properly determined by the fiqh commission at the islamic conference organization number 107 on 17-23 sya’ban in 1410 H.